(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the best of messengers, Muhammad Al-Amin, and upon his good and pure family, and whoever clings to his religion and his honorable household until the Day of Judgment, and after: